2009
DOI: 10.1039/b805648j
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalysed Negishi cross-coupling reactions: scope and mechanisms

Abstract: The Negishi cross-coupling of organozinc reagents is a valuable tool for the formation of C-C bonds in the presence of functional groups. Although this reaction is catalysed by Ni or Pd complexes, the latter have been much more developed. Nevertheless, Ni derivatives have become important in recent years, especially for their activity in the formation of alkyl-alkyl bonds. The mechanisms involved in Ni-catalysed reactions are different from the usual catalytic cycle involving oxidative addition-transmetalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
189
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(195 citation statements)
references
References 39 publications
(40 reference statements)
5
189
0
1
Order By: Relevance
“…[14] However, this crucial reaction step succeeded only after optimization, [15] because initially we obtained regioisomer 13 as a mixture of diastereomers. We found that the added sodium chloride must be ground first in order to generate the cross-coupling product 12 in good yield and high diastereomeric ratio (d.r.…”
mentioning
confidence: 99%
“…[14] However, this crucial reaction step succeeded only after optimization, [15] because initially we obtained regioisomer 13 as a mixture of diastereomers. We found that the added sodium chloride must be ground first in order to generate the cross-coupling product 12 in good yield and high diastereomeric ratio (d.r.…”
mentioning
confidence: 99%
“…As in the case of palladium, the fundamentals of these reactions were disclosed more than 30 years ago [196]. Developments over the past decade in nickel catalysis for the Negishi coupling of aryl and heteroaryl and to a minor extent alkenylzinc reagents have been directed toward achieving enhanced reaction scope.…”
Section: Nickel-catalyzed Cross-coupling Reactionsmentioning
confidence: 99%
“…However, often disregarded and considered less practical than palladium catalysis, it is not until recently that the use of nickel catalysis to couple C(sp 3 )-organozincs has regained interest, and that its distinctive features had led to the introduction of powerful variants to palladium catalysis. This is especially true in the challenging field of C(sp 3 )-C(sp 3 )-bond-forming reactions [124,126,196,276].…”
Section: Nickel-catalyzed Cross-coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these findings suggest that the transmetallation step occurs before the activation of the aryl halide and that Scheme 5. 44 Proposed mechanism for the carbon-carbon bond formation from (aryl)(alkyl)nickel(II) species in the presence of phosphine ligands [123,124].…”
Section: Cross-coupling With C(sp 2 )-Electrophilesmentioning
confidence: 99%